2016
DOI: 10.1093/hmg/ddw046
|View full text |Cite
|
Sign up to set email alerts
|

Defining functional classes of Barth syndrome mutation in humans

Abstract: The X-linked disease Barth syndrome (BTHS) is caused by mutations in TAZ; TAZ is the main determinant of the final acyl chain composition of the mitochondrial-specific phospholipid, cardiolipin. To date, a detailed characterization of endogenous TAZ has only been performed in yeast. Further, why a given BTHS-associated missense mutation impairs TAZ function has only been determined in a yeast model of this human disease. Presently, the detailed characterization of yeast tafazzin harboring individual BTHS mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 57 publications
(85 reference statements)
1
71
0
Order By: Relevance
“…The mouse monoclonal antibody raised against TAZ (Clone 2G3F7) was affinity purified by Steven Claypool’s laboratory at the Johns Hopkins University School of Medicine (15). …”
Section: Methodsmentioning
confidence: 99%
“…The mouse monoclonal antibody raised against TAZ (Clone 2G3F7) was affinity purified by Steven Claypool’s laboratory at the Johns Hopkins University School of Medicine (15). …”
Section: Methodsmentioning
confidence: 99%
“…His-77 is located in the HX 4 D motif, a conserved structural motif in acyltransferase, and the H77Q mutant is a typical example of the class 4 mutants (23). We prepared the H77Q mutant and isolated and determined its transacylation activity in the reaction PC (18: (42) recently demonstrated that the human equivalent of the H77Q mutant (H69Q in human) remarkably lacks the transacylation activity, indicating conservation of the functional importance of this histidine.…”
Section: Dilyso-cl Functions As An Acyl Acceptor From Pc-mentioning
confidence: 99%
“…The ‘reduced OsO 4 ’ procedure, which involves addition of 1% (wt/vol) potassium ferrocyanide immediately prior to staining and produces stronger contrast on membranes relative to other cellular components, has also been used for staining DAB reaction product from APEX2 (refs. 23,24). Finally, Joesch et al reported that reducing tissue samples using sodium hydrosulfite before OsO 4 staining greatly enhances the EM-level contrast of APEX2 staining 41 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, we confirmed that a fusion of APEX to the mitochondrial calcium uniporter was functional for transporting calcium into the mitochondrial matrix 12 . Claypool and co-workers examined lipid metabolite ratios to confirm the activity of an APEX2 fusion to tafazzin, a transacylase enzyme 24 . Sandin and co-workers showed that an APEX2 fusion to the protein caveolin rescued the formation of caveole 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation